Trust-like mechanisms - effective tools for boosting the competitiveness of the EU - theoretical and terminological insights - Irina Gvelesiani (CES Working Papers, 2017)
Today the EU is being confronted with internal and external economic challenges. They may become a threat of European stability. Significant strategies must be implemented for the promotion of a sustainable development reflected in economic resilience. The paper deals with the question of boosting the competitiveness of the EU via a rapid implementation of the trust-like mechanisms - “analogues” of the common law trust. It is mainly oriented on the method of a comparative analysis and presents certain prorated fruitful ways of rapid implementation of the trust-like devices in civil law jurisdictions. The outcomes of the paper will be useful for the successful planning of the European entrusting processes, because they indicate to the necessity of the implementation of the American models of mutual funds and the beginning of the utilization of an express trust, which will serve a great variety of socio-economic purposes.
Keywords: 330; economy; law; strategy; trust; trust-like device